Construction and Application of Clothing Pattern Design Model Based on Directed Graph Method (Journal of Fiber Bioengineering and Informatics, 2023)
At present, the intelligent design of clothing patterns still needs to rely on the experience of the patternmaker, and it cannot liberate the pattern maker from the complicated design work. The efficiency andflexibility of the design of clothing patterns are not high. In order to realize the intelligent pattern designof design knowledge automation, a directed graph method is proposed to construct a clothing patterndesign model, and the model is used to analyze the clothing pattern. In view of the characteristics ofclothing pattern design, the directed graph method is used to record the pattern design process, and themodel of clothing pattern design is constructed. The model is accurately analyzed by decomposing theoriginal model of clothing pattern design into sub-models of each structural line. Application examplesverify the feasibility of constructing a pattern design model and application by the directed graph method.The research results show that the pattern design model can clearly express the pattern design processand the valuable experience involved, and can accurately and quickly analyze the pattern. This researchcan provide a way to extract, collect, process, share and reuse pattern design knowledge for intelligentclothing design, and improve the efficiency of clothing pattern design.
Keywords: Directed Graph; Knowledge Automation; Clothing Pattern Design Model